CircBCAR3 sponges miR-27a-3p and mediates ferroptosis in human B-prolymphocytic leukaemia cells via SLC7A11: CircBCAR3 regulates ferroptosis in leukemia cells - Zhao, Guangwei; Chen, Huan; Luo, Jianmin (Cellular and Molecular Biology, 2023)
B-lymphocytic leukaemia is one of the most commonly diagnosed blood malignancies, and our knowledge of B-prolymphocytic leukaemia remained barely comprehensive. CircRNAs and miRNAs were identified of important regulatory roles in tumours. This study focused on the possibly existing interaction of circBCAR3 and miR-27a-3p, and downstream molecules thereafter in B-prolymphocytic leukaemia cells. CircBCAR3 and miR-27a-3p expression was evaluated in JVM-2 cell line and normal lymphocytes. Dual-luciferase luminescence assay was conducted for validation of circBCAR3 and miR-27a-3p interaction, as well as western blot and flow cytometry for evaluation and validation of their association with SLC7A11, reactive-oxygen species and Fe2+ regarding ferroptosis. CircBCAR3 were upregulated in JVM-2 cells and were reversely correlated with the expression of miR-27a-3p. CircBCAR3 targeted at miR-27a-3p and was consequently associated with SLC7A11 expression positively, inhibiting ferroptosis and peroxidative damage in JVM-2 cells. This study identified a circBCAR3-miR-27a-3p-SLC7A11 axis regulating ferroptosis and peroxidation of B-prolymphocytic leukaemia cells which might be a key mechanism facilitating the survival of tumour cells. However, further validation based on more diverse cell lines and animal models might be required.